The Relationship between Quality of Life and Health Literacy among Nurses of the Largest Heart Center in the North West of Iran - Marzieh Kheiri; Mohammad Hosien Taghdisi; Tahereh Dehdari; Saeideh Rnajbar; Nader Mahdavi; Ali Nazarpouri; seyedhadi mousavi (Mashhad University of Medical Sciences, 2019)
Background and Objective: Quality of life is a multidimensional concept which is influenced by several important factors, such as physical and mental status. Health literacy is also one of the factors with a significant impact on quality of life. The purpose of this study was to investigate the relationship between quality of life and health literacy of nurses in the largest heart center in northwest of Iran in 2018. Materials and Methods: This was a descriptive cross-sectional study performed on 217 nurses working in the largest heart center of Tabriz. The study data were collected using the 36-item Quality of Life Questionnaire (SF-36) and the Health Literacy for Iranian Adults (HELIA) questionnaire. Data analysis was performed using ANOVA, Pearson correlation test, and SPSS 25 software. Results: The overall mean and standard deviation of nurses' quality of life of (59.7 ± 17.6) were obtained and the majority of the subjects (84.7%) had a good quality of life. Also the overall mean and standard deviation of health literacy were estimated at (75.9 ± 13.3) which indicate adequate level of health literacy in nurses. There was a significant relationship between different dimensions of quality of life and total score of health literacy (P <0.001), but there was no significant relationship between understanding and perception of health literacy with most of the dimensions of quality of life. Conclusion: Findings showed that increasing nurses' health literacy had a positive effect on some aspects of their quality of life. Therefore, nursing supervisors should pay attention to health and quality of life while communicating with nursing staff and, try to improve nurses' quality of life by developing educational programs and promoting their health literacy.